Lead contamination from gold mining in Yellowknife Bay (Northwest Territories), reconstructed using stable lead isotopes. (April 2020) - Pelletier, Nicolas; Chételat, John; Cousens, Brian; Zhang, Shuangquang; Stepner, Dan; Muir, Derek C.G.; Vermaire, Jesse C.
Abstract: The contributions of contaminant sources are difficult to resolve in the sediment record using concentration gradients and flux reconstruction alone. In this study, we demonstrate that source partitioning using lead isotopes provide complementary and unique information to concentration gradients to evaluate point-source releases, transport, and recovery of metal mining pollution in the environment. We analyzed eight sediment cores, collected within 24 km of two gold mines, for Pb stable isotopes, Pb concentration, and sediment chronology. Stable Pb isotope ratios ( 206 Pb/ 207 Pb, 208 Pb/ 204 Pb) of mining ore were different from those of background (pre-disturbance) sediment, allowing the use of a quantitative mixing model. As previously reported for some Arctic lakes, Pb isotope ratios indicated negligible aerosol inputs to sediment from regional or long-range pollution sources, possibly related to low annual precipitation. Maximum recorded Pb flux at each site reached up to 63 mg m −2 yr −1 in the period corresponding to early years of mining when pollution mitigation measures were at a minimum (1950s–1960s). The maximum contribution of mining-derived Pb to these fluxes declined with distance from the mines from 92 ± 8% to 8 ± 4% at the farthest site. Mining-derived Pb was still present at the sediment surface within 9 km of Giant Mine more than ten years after mine closure (5–26 km, 95% confidence interval) and model estimates suggest it could be present for another ∼50–100 years. These results highlight the persistence of Pb pollution in freshwater sediment and the usefulness of Pb stable isotopes to quantify spatial and temporal trends of contamination from mining pollution, particularly as concentrations approach background. Graphical abstract: Image 1 Highlights: Pb isotopes revealed mining-derived Pb reached at least 24 km south of the source. Long-range/regional aerosols were a negligible Pb source to lake sediment. Mining-derived Pb is still present in surface sediment 9 km from the source. Sediment burial of Pb estimated to take 46–97 yrs after mine closure in nearfield. Abstract : Lead isotopes are an effective tool for quantifying the spatial extent of mining pollution as well as source-specific flux and persistence of lead in lake sediments.